2019
DOI: 10.17645/si.v7i4.2346
|View full text |Cite
|
Sign up to set email alerts
|

Syrian Refugee Entrepreneurship in Turkey: Integration and the Use of Immigrant Capital in the Informal Economy

Abstract: This study focuses on small-scale entrepreneurship of Syrian refugees in Turkey. It analyses in a Bourdieusian way how they utilize cultural, social, economic and symbolic capital, and reveals their start-up and sustainability strategies. It is based on 24 in-depth interviews with Syrian small entrepreneurs who started up new businesses after 2011, in Istanbul, Gaziantep, and Hatay. It describes the entrepreneurial opportunity structure and the significance of the informal economy and analyses Syrians’ utiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 19 publications
0
16
0
3
Order By: Relevance
“…Migrants’ personal savings are a crucial source of funds for opening a business (Rahman, 2018). Atasü-Topcuoğlu (2019) conducted a study amongst Syrian small entrepreneurs in Istanbul and found that as informal entrepreneurship is not well-integrated with municipal regulatory systems, informal ventures are likely to remain small. Immigrant entrepreneurs’ primary concerns are to provide informal jobs and earn money for daily survival.…”
Section: Resultsmentioning
confidence: 99%
“…Migrants’ personal savings are a crucial source of funds for opening a business (Rahman, 2018). Atasü-Topcuoğlu (2019) conducted a study amongst Syrian small entrepreneurs in Istanbul and found that as informal entrepreneurship is not well-integrated with municipal regulatory systems, informal ventures are likely to remain small. Immigrant entrepreneurs’ primary concerns are to provide informal jobs and earn money for daily survival.…”
Section: Resultsmentioning
confidence: 99%
“…The contributions in this issue explore different mechanisms and processes of social inclusion that the accumulation of migrant capital entails, emphasising the strategies and opportunities used by the members of migrant communities during the migration process. The authors approach migrant capital as a resource that becomes available to migrants during their migration process (Atasü-Topcuoğlu, 2019;Glorius, 2019;Hiitola, 2019) and as one that is created by migrants because of their migration (Koikkalainen, 2019;Wahlbeck & Fortelius, 2019). Migrant capital is also shown to be available to migrants' family members via their transnational ties (Dís Skaptadóttir, 2019;Saksela-Bergholm, 2019;Toivanen, 2019).…”
Section: The Contributionsmentioning
confidence: 99%
“…The analysis in the articles considers both strategies and opportunities utilised by migrants and members of transnational communities in diverse economic, social and political context. As the articles show, transnational networks can be used by migrants and their family members to achieve occupational, economic and educational advantages (Atasü-Topcuoğlu, 2019;Dís Skaptadóttir, 2019;Glorius, 2019;Koikkalainen, 2019;Toivanen, 2019;Wahlbeck & Fortelius, 2019). They can also be useful in their attempts to reunite with family members (Hiitola, 2019) or to have access to informal social protection and care arrangements (Saksela-Bergholm, 2019) in both the sending and receiving societies.…”
Section: The Contributionsmentioning
confidence: 99%
“…For instance, thousands of Syrian companies have been established in Turkey and the capital outflow from Syria to Turkey has reached billions of US dollars (Amos, 2013; TEPAV, 2019). Yet, the situation of Syrian businesspeople within the refugee waves has scarcely been examined, other than with regard to their motivations and challenges in conducting business in Turkey (Alrawadieh, Karayilan, & Cetin, 2019; Atasü‐Topcuoğlu, 2019; Shneikat & Alrawadieh, 2019).…”
Section: Introductionmentioning
confidence: 99%